Utilization of Fermented Feather Meal as a Replacement of Fish Meal in the Diet of Hybrid Clarias Catfish - Chumlong Arunlertaree; Ek Rakyuttithamkul (Agriculture and Natural Resources, 2006)
The suitability of replacing fish meal in the hybrid clarias catfish diet with fermented feather meal was evaluated. The fermentation by yeast was performed to increase efficiency of feather meal. Five diets were formulated with diet 1 containing 100 % fish meal (control diet) and diet 2, 3, 4 and 5 were 25 %, 50 %, 75 %, and 100 % of fermented feather meal replacement of fish meal in the diet formula respectively. The results showed that average final weight (125.72±10.65 to 132.67±6.91 g), average daily weight gain (0.92±0.20 to 1.05±0.12 g/ind/day), feed conversion ratio (FCR) (2.62±0.30 to 2.97±0.62) and apparent net protein retention (ANPR) (25.43±4.51 to 29.86±2.89 %) of hybrid clarias catfish fed with diet formulas 1, 2 and 3 were not significantly different (P>0.05). Meanwhile, protein efficiency ratio (PER) (0.91±0.04 to1.26±0.15) and protein intakes (PI) (45.23±0.41 to 50.88±0.486.91 g/ind) were not significantly different (P>0.05) among hybrid clarias catfish fed with diet formulas 1, 2, 3 and 4. Survival rate (100 %) was not significantly different (P>0.05) among all treatments. This study suggested that the percentage of fish meal replacement with fermented feather meal in hybrid clarias catfish diet at 25 % had a close growth and feeding efficiency to fish meal diet and was not significantly different from fish fed with the control diet. The 25 % of replacement fish meal by fermented feather meal could reduce diet cost by about 0.81 baht/kg.